Wokół pierwszego pobytu Apostoła Pawła w Efezie (Dz 18,18-22) - Siuda, Tomasz (Wydział Teologiczny UAM, 2010)
One of the crucial stages of the Apostle Paul’s ministry was his stay at Ephesus. However, considering the fact that the reliability of some data in the Acts of the Apostles on the time of Paul’s arrival to Ephesus is nowadays frequently put into question, it has become necessary to investigate the issue. In the present article the author assesses the relevant source material and takes a stand on the particular opinions of contemporary interpreters of the subject. Based on an analysis of the text of the Acts of the Apostles he is led to conclude that Luke’s account of Paul’s first short visit to Ephesus reveals traits of historicity.
On the Apostle Paul's First Stay at Ephesus (Acts 18:18-22)
Keywords: Apostle Paul; Ephesus; Priscilla and Aquila